Nurses' Expectations of Clinical Supervision in Hospitals : A Qualitative Study - Ningsih, Ropika (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2025)
ABSTRACT Background: Clinical supervision at the hospital is suboptimal due to non-compliance with standard procedures. The supervising department head lacks adherence to supervision principles, proper steps, and a designated supervision schedule. One of the key managerial responsibilities of the head of a department is the supervision of operation. Supervision of nursing clinics is still a problem that must be handled in hospitals, because it is still considered a scary thing by nurses because there are still nurses in hospitals who assume supervision is a scary thing, supervision finds errors and supervision makes nurses suddenly surprised because it is still not scheduled. Objective: This study aims to explore nurses' expectations regarding the implementation of clinical supervision in hospitals. Methode: This study employed the phenomenological approach with purposive sampling technique to select 30 nurses as participants. Data collection involved focused discussion groups organized into five groups. Each group was carried out a focus group discussion for 60 minutes. The primary focus of this study is on interpreting data related to the research location. The research was conducted at a government hospital in West Sumatra province during September 2022. After data collection, researchers process the data manually, and then analyze the data for interpretation. Result: Three key themes emerged from the study: the purpose of clinical supervision, nurses' perceptions of clinical supervision, and expectations for its implementation. Conclusion: It can be concluded that nurses expect clinical supervision to be effective, straightforward, and integrated with technology. Nurses also expect scheduled and non-sudden supervision. Keywords: Nurse expectations, hospital, clinical supervision.